STRATEGI PENGEMBANGAN BUDIDAYA KEPITING BAKAU (Scylla serrate) PADA VEGETASI MANGROVE DI KABUPATEN INDRAGIRI HILIR - Deby Kurnia (Indonesian Journal of Agricultural Economics, 2016)
Conservation of mangrove vegetation is important in the high levels of economic dependence of the community on the vegetation. Crab Farming is one of the alternative environmental conservation. This research aimed to formulate strategy of Mangrove Crab cultivation development on mangrove vegetation in Indragiri Hilir Regency. The collected data were analyzed by composite. The combination of these two analyzes provides more quantitative assessment than just using the SWOT Analysis. Strategies can be grouped by priority level. There are 3 (three) efforts that are classified as strategic in business development that is (1) facilitation of third party (stakeholders) that can provide subsidy, feed subsidy, and other input subsidy), (2) improvement of knowledge and skill of fisherman through technical guidance of cultivation Mangrove crabs around the mangrove vegetation, (3) Strengthening of fishermen/farmer institutions through the formation of farmer groups of mangrove crabs.Keyword: Strategy, Crab, Mangrove Vegetation